Sec14 like PITPs couple lipid metabolism with phosphoinositide synthesis to regulate golgi functionality - Mousley, Carl; Davison, J.; Bankaitis, V. (Springer New York, 2015)
An interface coordinating lipid metabolism with proteins that regulate membrane trafficking is necessary to regulate Golgi morphology and dynamics. Such an interface facilitates the membrane deformations required for vesicularization, forms platforms for protein recruitment and assembly on appropriate sites on a membrane surface and provides lipid co-factors for optimal protein activity in the proper spatio-temporally regulated manner. Importantly, Sec14 and Sec14-like proteins are a unique superfamily of proteins that sense specific aspects of lipid metabolism, employing this information to potentiate phosphoinositide production. Therefore, Sec14 and Sec14 like proteins form central conduits to integrate multiple aspects of lipid metabolism with productive phosphoinositide signaling.